Microstructure of brushite crystals prepared via high internal phase emulsion - Lim, Hong Ngee; Kassim, Anuar; Huang, Nay Ming; Chia, Chin Hua (Versita Warsaw and Springer, 2010)
For the first time, various microstructures of calcium phosphates were successfully synthesized using a high internal phase emulsion process. The crystals were possessed in the brushite crystalline phase. The morphology of the crystals was influenced by the variables related to the emulsion process route, which consisted of flakes, dendrites and particulates structures.